Incidence and determinants of medication errors and adverse drug events among hospitalized children in West Ethiopia - Dedefo, Mohammed Gebre; Mitike, Abraham Haileamlak; Angamo, Mulugeta Tarekegn (BMC pediatrics, 2016)
Background Medication errors cause a large number of adverse drug events with negative patient health outcomes and are a major public-health burden contributing to 18.7–56 % of all adverse drug events among hospitalized patients. The aim of this study was to assess the incidence and determinants of medication errors and adverse drug events among hospitalized children. Methods A prospective observational study was conducted among hospitalized children in the pediatrics ward of Nekemte Referral Hospital from February 24 to March 28, 2014. Data were collected by using checklist guided observation and review of medication order sheets, medication administration records, and other medical charts of the patients. To identify the independent predictors of medication errors and adverse drug events, backward logistic regression analysis was used. Statistical significance was considered at p -value <0.05. Results Out of 233 patients who were included in the study, 175 (75.1 %) of patients were exposed to medication errors. From the 1,115 medication orders reviewed, 513 (46.0 %) medication errors, 75 (6.7 %) potential adverse drug events and 17 (1.5 %) actual adverse drug events were identified. Of the 17 adverse drug events, eight (47.0 %) were preventable while nine (53.0 %) were not. Most medication errors were dosing errors (118; 23.0 %), followed by wrong drug (109; 21.2 %) and wrong time of administration (79; 15.4 %). On multivariable logistic regression analysis, length of hospital stay of ≥ 5 days (AOR = 4.2, 95 % CI = 1.7-10.4, p = 0.002), and number of medication of 4–6 (AOR = 4.9, 95 % CI = 2.3-10.3, p < 0.001) and number of medication of ≥7 (AOR = 10.4, 95 % CI = 3.0-35.9, p < 0.001) were independent predictors of medication errors; and length of hospital stay of ≥ 5 days (AOR = 3.5, 95 % CI = 1.2-10.1, p = 0.023) and number of disease conditions =2 (AOR = 4.6, 95 % CI = 1.4-15.1, p = 0.014) were independent predictors of adverse drug events. Conclusion Medication errors and adverse drug events are common on the pediatrics ward of Nekemte Referral Hospital. In particular, children with multiple medications and longer hospital stays, and those with co-morbidities and longer hospital stays, were at greater risk for medication errors and adverse drug events, respectively.